A remarkable new species of Paraphamartania Engel from Portugal (Diptera, Asilidae) - Mortelmans, Jonas; Tomasovic, Guy; Nagy, Zoltán Tamás (Zootaxa, 2014)
Paraphamartania marvaoensis sp. nov. is described based on three male and one female specimens from Marvão, Portugal. The discovery of this new species of Paraphamartania is of great significance since it shows the occurrence of a second species of Paraphamartania in the western Mediterranean. High resolution pictures of type material of all three species of Paraphamartania are provided together with a key to these three species. DNA barcodes of this new species are provided, so future workers are able to study relationships of Paraphamartania.